The need to incorporate the impact of population ageing into the post-COVID-19 policy and planning reset in Low and Middle Income Countries. Issue 1 (1st January 2021) - Solanki, Geetesh; Kelly, Gabrielle; Cornell, Judith; Geffen, Leon; Doherty, Tanya
ABSTRACT: The COVID-19 pandemic is likely to widen the health care demand-supply gap, especially in low- and middle-income countries (LMICs). The virus has had the greatest impact on older persons in terms of morbidity and mortality, and is occurring at a time of rapid population ageing, which is happening three times faster in LMICs than in high-income countries. Addressing the demand-supply gap in a post-COVID-19 era, in which resources are further constrained, will require a major 'reset' of the health system. In this article, we argue that the impact of ageing populations needs to be factored into the post-COVID-19 policy and planning reset including explicit, transparent prioritisation processes.